Thermally induced all-optical ferromagnetic resonance in thin YIG films - Eva Schmoranzerová; Jozef Kimák; Richard Schlitz; Sebastian T B Goennenwein; Dominik Kriegner; Helena Reichlová; Zbyněk Šobáň; Gerhard Jakob; Er-Jia Guo; Mathias Kläui; Markus Münzenberg; Petr Němec; et al. (New Journal of Physics, 2023)
All-optical ferromagnetic resonance (AO-FMR) is a powerful tool for the local detection of micromagnetic parameters, such as magnetic anisotropy, Gilbert damping or spin stiffness. In this work we demonstrate that the AO-FMR method can be used in thin films of yttrium iron garnet (YIG) if a metallic capping layer (Au, Pt) is deposited on top of the film. Magnetization precession is triggered by heating of the metallic layer with femtosecond laser pulses. The heat pulse modifies the magneto-crystalline anisotropy of the YIG film and shifts the quasi-equilibrium orientation of the magnetization, which results in precessional magnetization dynamics. The laser-induced magnetization precession corresponds to a uniform (Kittel) magnon mode, with the precession frequency determined by the magnetic anisotropy of the material as well as the external magnetic field, and the damping time set by a Gilbert damping parameter. The AO-FMR method thus enables measuring local magnetic properties, with a resolution given by the laser spot size.